An FMEA-based TOPSIS approach under single valued neutrosophic sets for maritime risk evaluation: the case of ship navigation safety - Bashan, Veysi; Demirel, Hakan; Gul, Muhammet (SPRINGER, 2020)
As in terrestrial facilities, safety is one of the most important issue in ships. Vessels navigating in many parts of the world face many different, tough and dangerous navigational risks. In this context, twenty-three fundamental risks which are frequently encountered in ship navigation were considered in this study and examined by an FMEA-based TOPSIS approach under single valued neutrosophic sets. Because of the lack of data in the literature, the opinions of the experts (Masters) who have many years of experience in the sector were taken. As a result of the study, extreme weather conditions, injury of crew, loss of input of sensory equipment (depth, gyro, speed etc.), struck by ropes, exposure to high speed machineries under high pressures, loss of maneuverability are very important among these risks. Considering these risks, corrective-preventive action plans and managerial implications for ship navigation have been presented. Consequently, the results of this study have an important warning and solution recommendation regarding ship navigation risks.
Keywords: Risk assessment; Neutrosophic sets; FMEA; TOPSIS; Maritime industry; Ship navigation; GROUP DECISION-MAKING; FAILURE MODE; COLLISION-AVOIDANCE; FUZZY TOPSIS; PROBABILISTIC RISK; AHP METHODS; SELECTION; SYSTEM; TRANSPORTATION; PRIORITIZATION; Computer Science